2020
DOI: 10.3389/fphar.2020.590929
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Attenuates Atherosclerosis and Plays an Anti-Inflammatory Role in ApoE Knock-Out Mice and Bone Marrow-Derived Macrophages

Abstract: Amygdalin, the main component of Prunus persica (L.) Stokes, has been used to treat atherosclerosis in mouse model due to its anti-inflammatory role. However, the underlying mechanism remains poorly understood. This study aimed to evidence the influence of amygdalin on high-fat diet-induced atherosclerosis in ApoE knock-out (ApoE −/− ) mice, and unravel its anti-inflammatory mechanism. ApoE −/− mice fed with high-fat diet for eight weeks were randomly divided into four groups and injected with amygdalin at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…According to MS spectrum and retention times of UPLC-Q-TOF/MS analysis, peaks of QJWJ were tentatively identified as Coixol (Supplementary Figure S2), Asperglaucide (Supplementary Figure S3), and Amygdalin (Supplementary Figure S4) in negative ion mode, Tricin (Supplementary Figure S5) in positive ion mode. Taken together, the major chemical active components of QJWJ were Coixol, Asperglaucide, Amygdalin, and Tricinj, which were consistent with previous studies (Gao et al, 2009;Fan et al, 2015;Wang et al, 2020;Li et al, 2021).…”
Section: Major Chemical Active Components Of Qjwjsupporting
confidence: 92%
“…According to MS spectrum and retention times of UPLC-Q-TOF/MS analysis, peaks of QJWJ were tentatively identified as Coixol (Supplementary Figure S2), Asperglaucide (Supplementary Figure S3), and Amygdalin (Supplementary Figure S4) in negative ion mode, Tricin (Supplementary Figure S5) in positive ion mode. Taken together, the major chemical active components of QJWJ were Coixol, Asperglaucide, Amygdalin, and Tricinj, which were consistent with previous studies (Gao et al, 2009;Fan et al, 2015;Wang et al, 2020;Li et al, 2021).…”
Section: Major Chemical Active Components Of Qjwjsupporting
confidence: 92%
“…Recent studies have shown that MAPKs signaling pathway is activated to attenuate inflammation in AS ( Wang et al, 2020a ; Wang et al, 2020b ; Lu et al, 2020 ), making MAPKs an ideal target of drug therapy. NF-κB, a critical transcription factor in inflammatory responses, can be activated by ox-LDL to promote AS ( Chávez-Sánchez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, NOS1 also regulates dendritic cell maturation in humans and is required for iNOS expression in allergen-induced asthma in mice [ 10 , 11 ]. In oxidized low-density lipoprotein (oxLDL)-induced bone marrow-derived macrophages (BMDMs), the levels of inflammatory cytokines IL6 and TNFα were associated with NOS1 expression [ 12 ]. In addition, inflammation can be promoted by NOS1-synthesized NO at lower concentrations [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%